Ionic liquid as antibacterial agent for an experimental orthodontic adhesive. Issue 8 (August 2019) - Martini Garcia, Isadora; Jung Ferreira, Carolina; de Souza, Virgínia Serra; Castelo Branco Leitune, Vicente; Samuel, Susana Maria Werner; de Souza Balbinot, Gabriela; de Souza da Motta, Amanda; Visioli, Fernanda; Damiani Scholten, Jackson; Mezzomo Collares, Fabrício
Highlights: Brackets were adhered to enamel with new antibacterial orthodontic adhesives. Ionic liquid was used as antibacterial agent for the first time in a dental resin. Ionic liquid at 15 wt.% showed higher antibacterial property against S. mutans . The mechanical and bond strength of adhesives were not affected by ionic liquid. All orthodontic adhesives showed no cytotoxicity against human keratinocytes. Abstract: Objective: The aim of this study was to formulate and evaluate experimental orthodontic adhesives with different concentrations of 1 -n- butyl-3-methylimidazoilium bis(trifluoromethanesulfonyl)imide (BMIM.NTf2 ). Methods: The experimental orthodontic adhesives were formulated with methacrylate monomers, photoinitiators and silica colloidal. The ionic liquid BMIM.NTf2 was synthesized and characterized. BMIM.NTf2 was added at 5 (G5% ), 10 (G10% ) and 15 (G15% ) wt.%. One group contained no BMIM.NTf2 to function as control (GCtrl ). The adhesives were evaluated for polymerization kinetics, degree of conversion (DC), Knoop hardness and softening in solvent, ultimate tensile strength (UTS), shear bond strength (SBS), thermogravimetric analysis (TGA), antibacterial activity and cytotoxicity. Results: BMI.NTf2 showed the characteristic chemical peaks. The polymerization kinetics were different among the groups. G10% and G15% showed higher DC (p < 0.05). G5% and GCtrl had no differences for softening in solvent (p > 0.05). There were no differences for UTS (p > 0.05) and SBS (p > 0.05). TGA showed one different peak for G15% . All groups with BMIM.NTf2 showed antibacterial activity compared to GCtrl (p < 0.05) without cytotoxicity (p > 0.05). Significance: To reduce biofilm formation around brackets and to prevent demineralization at susceptible sites, materials have been developed with antibacterial properties. In this study, a new experimental orthodontic adhesive was formulated with an imidazolium ionic liquid (BMIM.NTf2 ) as antibacterial agent. The incorporation of 5 wt.% of ionic liquid decreased biofilm formation without affecting the physico-chemical properties and cytotoxicity of an experimental orthodontic resin.